Measurement of the B̄0 lifetime and the B0B̄0 oscillation frequency using partially reconstructed B̄0→D*+ℓ- ν̄ℓ decays - Aubert, B; Barate, R; Boutigny, D; Couderc, F; Karyotakis, Y; Lees, J; Poireau, V; Tisserand, V; Zghiche, A; Grauges, E; Palano, A; Pappagallo, M; et al. (2006)
We present a simultaneous measurement of the B̄0 lifetime τB0 and B0B̄0 oscillation frequency Δmd. We use a sample of about 50000 partially reconstructed B̄0→D*+ℓ-ν̄ℓ decays identified with the BABAR detector at the PEP-II e+e- storage ring at SLAC. The flavor of the other B meson in the event is determined from the charge of another high-momentum lepton. The results are τB0=(1.504±0.013(stat)- 0.013+0.018(syst))ps, Δmd=(0.511±0.007(stat)-0.006+0.007(syst))ps- 1. © 2006 The American Physical Society.